Obituary: Homage to Edward Thompson, Part I - Palmer, Bryan D. (Labour/Le Travail, 1993)
The article provides a detailed appreciation of the life and work of British historian E. P. Thompson (1924-1993), a leading figure in the historians' group of the British Communist Party.